RF Systems, Circuits and Components - Bin Ibne Reaz, Mamun; Arif Sobhan Bhuiyan, Mohammad (IntechOpen, 2019)
Radio frequency (RF) refers to frequencies between the upper limit of audio frequencies (> 20 KHz) and the lower limit of infrared frequencies (< 300 GHz). The increased popularity and easy operation of RF devices for different end users and corporate applications such as RFID, Bluetooth, Zigbee and Wi-Fi devices and sensors have raised the demand for small power and less off-chip components that tend to achieve integrated circuits with added security and convenience. Concurrent technologies allow the scientists to reinvent low-power, high-performance and reliable RF systems, circuits and components for many home and commercial applications. The features of RF systems, circuits and components are still being researched and integrated in existing systems to create marketable and potential new RF products for more exciting applications.